Sensible Heat Balance Measurements of Soil Water Evaporation beneath a Maize Canopy. Issue 2 (8th April 2014) - Xiao, X.; Heitman, J.L.; Sauer, T.J.; Ren, T.; Horton, R.
Abstract : Soil water evaporation is an important component of the water budget in cropped fields; few methods are available for continuous and independent measurement. A sensible heat balance (SHB) approach has been demonstrated for continuously determining soil water evaporation under bare surface conditions. Applicability of SHB measurements beneath a crop canopy cover has not been evaluated. We tested SHB using heat‐pulse sensors to estimate evaporation beneath a full maize ( Zea mays L.) canopy. We also implemented a modified SHB approach incorporating below‐canopy net radiation, which extended the range of conditions under which SHB is applicable. Evaporation was measured at three positions: row (R), interrow (I), and interrow with roots excluded (IE). Evaporation rates were generally small, averaging <0.7 mm d −1 across all dates, positions, and measurement methods during the drying period. The SHB evaporation estimates varied among R, I, and IE, with cumulative totals of 4.4, 7.4, and 7.9 mm, respectively, during a 12‐d drying period. Lower soil water contents from plant water uptake reduced evaporation rates at R more appreciably with time than at the other positions; I and IE provided similar evaporation patterns. The SHB evaporation estimates at R and I were compared with microlysimeter data on 8 d. Correlation between approaches was modest ( r 2 = 0.61) but significant ( p < 0.001) when compared separately at R and I positions. Correlation was improved ( r 2 = 0.81) when evaporation estimates were combined across positions, with differences between SHB and microlysimeters typically within the range of values obtained from microlysimeter replicates. Overall, the results suggest good potential for using SHB and modified SHB approaches to determine soil water evaporation in a cropped field. The SHB approach allowed continuous daily estimates of evaporation, separate from evapotranspiration and without destructive sampling.